Using Guided Writing Strategy Strategy in Teaching Descriptive Writing to the Tenth Grade Students - Nelly Megawati (Edukasi, 2020)
The objectives of the study were to find out whether or not there was a significant difference on the tenth grade students’ descriptive text writing who were taught by using Guided Writing Strategy Strategy and those who were not, and to find out whether or not there were significant differences on the tenth grade students’ descriptive writing in excellent, good, average and poor categories by using Guided Writing Strategy Strategy at SMA Muhammadiyah 6 Palembang. The population of this study consisted of 132 students of SMA Muhammadiyah 6 Palembang in the academic year of 2017/2018. There were 64 students taken as sample. Each class consisted of 32 students from class X.IPA A chosen as experimental group and class X.IPA C chosen as control group. The sample of this study was taken by using purposive sampling method. The instrument used in collecting the data was written test. The test was administered twice, as the pretest and posttest for both experimental and control group. The results of the test were analyzed by using independent sample t-test and Two-way ANOVA. From the result of the independent sample t-test, it was found that there was a significant difference from students’ posttest experimental and control group, since the p-output (0.002) was lower than 0.05. From the result of the Two-way ANOVA, it was found that there were significant differences on students’ descriptive text writing who were taught by using Guided Writing Strategy Strategy, since the p-output (0.197) was higher than 0.05. The result alsho showed that there was no significant interaction effect of students’descriptive writing in excellent, good, average and poor categories.